Development of a freeform surface editor - Oh, Patrick Kay Yew (2011)
Widely used as one of the primary industrial standards for surface modelling in computer aided design (CAD) and computer aided manufacturing (CAM) systems, Non Uniform Rational B-splines (NURBS) has presented itself with many useful properties on designing and modelling curves and surfaces. However, there still exists a major shortcoming in NURBS. The nature of NURBS rectangular structure requires that its control points must always align itself in a rectangular grid, thus having the requirement of adding unnecessary control points, which serves no other purpose but only to fulfill its rectangular control grid topology. With the large amount of superfluous control points, it complicates the design process, and as a result, it greatly increases the amount of time and effort needed to model and edit a freeform surface.